Redescription and new records of Jansen’s goatfish, Parupeneus jansenii (Mullidae), from the Western Pacific and Eastern Indian Ocean - Uiblein, Franz; Hoang, Tuan Anh; Gledhill, Daniel (Zootaxa, 2017)
For Jansen’s goatfish, Parupeneus jansenii (Mullidae), taxonomic knowledge has been rather poor and occurrence information restricted to a few localities only, with verified records from northern Sulawesi and Sunda Street (Indonesia), and Luzon (Philippines). This species is here included in the so-called “heptacanthus” group together with the Indo-Pacific cinnabar goatfish, P. heptacanthus, and five Indian Ocean congenerics, based on an evenly, symmetrically rounded posterior maxilla margin and similarities in meristic characters and preserved colour. In total 29 P. jansenii and 53 P. heptacanthus consisting of types, recently collected material from south-central Vietnam, southern Indonesia, and NE Australia, and geographically related reference material were studied along with single types of the other five heptacanthus-group species and P. angulatus, a morphologically similar Western Indian Ocean species. In total 62 quantitative meristic and morphometric characters including standard length (SL) were analysed after splitting the data into two size classes (small-sized fish, < 110 mm SL, vs. large-sized fish  > 110 mm SL) to account for size-related differences due to allometry. Diagnoses for P. jansenii and P. heptacanthus and a redescription for P. jansenii were prepared. Fresh-fish colour descriptions for both large- and small-sized voucher specimens of P. jansenii are provided and the effects of freshness status on colour patterns is documented. New records for P. jansenii for Vietnam, southern Indonesia and NE Australia (= first verified record for Australia) are reported and depth information (24–100 m depth range) is given for the first time. P. jansenii differs from the co-occurring P. heptacanthus - independently of size - in shallower body and caudal peduncle, smaller maximum head depth, shorter barbels, caudal and pelvic fins, shallower first dorsal fin, shallower first ray of second dorsal fin, and lack of small dark red or reddish-brown spot on or just below the eighth lateral-line scale. The populations of P. jansenii from Vietnam and Australia differ from each other in a single character, the height of the eighth dorsal-fin ray, but both overlap with the intermediate population from Indonesia. This comprehensive alpha-taxonomic approach provides a useful tool for uncovering the diversity of Parupeneus goatfishes.